Color symbolism and resistance in Shaila Abdullah’s Saffron Dreams - Djohar, Hasnul Insani; Komalasari, Lailla Sekar Dwi (citeus, 2024)
This study analyzes how Shaila Abdullah's Saffron Dreams portrays and resists Orientalists' stereotypes of Muslim women. Through Saffron Dreams, Abdullah attempts to put up a fight against the negative stereotypes of Orientalists toward Muslim women. It is shown based on how the main protagonist is portrayed as a Muslim Pakistani-American woman who lost her husband in 9/11, experiencing mistreatment from her host land society due to the spreading negative stereotypes of Muslim women. By utilizing Close Textual Analysis, this study focuses on examining how the novel depicts and resists the Muslim women's stereotype by Orientalists. This study discovers that the novel repeatedly portrays that Muslim women are perceived as oppressed by men and patriarchy who are forced to do arranged marriage and use hijab and also as the